Pathophysiological aspects of Sjögren's Syndrome: a narrative review (Research, Society and Development, 2023)
Sjögren's Syndrome (SS) is a systemic autoimmune disease characterized by the involvement of exocrine glands, in addition to the presence of signs/symptoms of systemic disease. The lacrimal and salivary glands are often affected, causing sicca syndrome, characterized by dryness of the eyes (xerophthalmia) and mouth (xerostomia). This article aims to address a pathophysiological line of SS in a clinical context. This study is a narrative review with the purpose of discussing and describing the pathophysiology of SS in its clinical context. The following databases were used: SciElo (Scientific Electronic Library Online) and PubMed (US National Library of Medicine), with language restriction (Portuguese) and prioritizing articles published between 2010 and 2022. Mononuclear cell infiltration, humoral factors such as antibodies and cytokines, which are described in the literature as responsible for causing a structural and, consequently, functional alteration of the exocrine gland, causing a marked decrease in the production of tears by the lacrimal glands and a decrease in the production of saliva by the salivary glands. In short, SS remains a significant burden on healthcare systems around the world. However, the advances made in understanding its pathophysiology in the last 20 years surpass everything that has gone before.